Experimental investigation and modelling of wax deposition inhibition in pipeline transportation of crude oil - Norida, Ridzuan (2016)
Wax deposition causes serious problems in crude oil flow assurance due to the long chain n-paraffin. The application of wax inhibitors is an effective method to prevent wax formation and deposition. In this thesis, seven commercial groups of wax inhibitors were introduced and their performances were evaluated through cold finger and rheological methods. From both methods, poly(ethylene-co-vinyl acetate) (EVA) showed the highest inhibition performance based on the reduction of the wax deposit amount and the decrement of the crude oil viscosity value. To substantiate even further in the wax inhibitor selected, molecular dynamics (MD) simulation was introduced to understand the interaction between wax crystals and wax inhibitor at the molecular level. The interaction of wax crystals with inhibitors were analysed through radial distribution function (rdf) value which described the structure of inhibitor in wax crystals. MD simulations confirmed the increased percentage of inhibition efficiency (PIE) of the experimental study using EVA. Thus, EVA had inhibited the formation of n-octacosane wax solid of crude oil better than poly(maleic anhydride-alt-1-octadecene) (MA). N-octacosane wax crystal is a long chain molecule of crude oil and it has a strong van der Waals (vdW) interaction between the carbonyl group in EVA and hydrogen atoms in the n-octacosane. This increases its solubility. In addition, EVA has strong vdW interaction via the oxygen atom in the vinyl acetate functional group with the hydrogen atom in n-octacosane, resulting in a higher probability value of inhibition (gxy(r)). Design of experiment (DOE) was used to screen four possible factors that contribute to the n-paraffin wax formation. The factor of cold finger temperature (B) was identified as the most significant factor of wax problem, followed by experimental duration (C), rotational speed (A) and inhibitor concentration (D). The combination effect between factors B and C showed the highest percentage of contribution of wax deposit formation. The optimisation of wax deposit formation was achieved using response surface methodology (RSM). The optimised conditions were obtained at 1.5 h and 25°C. The minimum value of wax crystal formation achieved after the optimisation and transformation was 0.0042 g. This value shows over 150-fold decrement of wax formation expression compared to prior the optimisation process. Therefore, the model obtained from RSM is useful to provide an insight for engineers or researchers to estimate wax formation at other conditions.